Lignin-containing Feedstock Hydrogenolysis for Biofuel Component Production - Elena Shimanskaya; Аntonina A. Stepacheva; Esther Sulman; Evgeny Rebrov; Valentina Matveeva (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
In this paper, the commercial 5%Pd/C and 5%Pt/C catalysts and synthesized 5%Pt/MN-270 and 5%Pd/MN-270 were used in the hydrogenolysis of lignocellulosic material (softwood sawdust) to obtain liquid fuels in the form of hydrocarbons. As lignin has a very complex structure, anisole was used as a model compound. It was found that the use Pt-containing catalysts based on hypercrosslinked polystyrene in both processes of anisole and lignin-containing feedstock conversion allowed obtaining the highest yield of oxygen-free hydrocarbons (up to 96 wt. %). Besides, the polymer based catalysts showed high stability in hydrogenolysis process in comparison with the commercial carbon based catalysts.